Numerical analysis of blade coating of a third-order fluid. (April 2019) - Bhatti, Saira; Zahid, Muhammad; Rana, Muhammad Afzal; Siddiqui, Abdul Majeed; Abdul Wahab, Hafiz
In this study, the blade coating process of a third-order fluid has been investigated. Flow between the narrow channel formed by the rigid blade and the web is generated due to the web motion and the constant pressure gradient. The governing equations of motion are simplified using lubrication approximation theory. We obtained analytical solutions for velocity field, pressure distribution, pressure gradient and coating thickness using perturbation method. How the model's dimensionless parameters affect velocity, pressure gradient, pressure and coating thickness are presented graphically and in tabulated form. We found that the third-order parameter provides a mechanism to control velocity, pressure, power input and the final coating thickness.